1992
DOI: 10.1002/1097-0142(19920201)69:3<636::aid-cncr2820690306>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of fibrinogen to enhance the antitumor effect of OK-432. A new approach to immunotherapy for colorectal carcinoma

Abstract: OK‐432 (5 KE), an immunomodulatory agent prepared from an attenuated strain of Streptococcus pyogenes, was dissolved in 1 ml of aprotinin (1000 KIE) and mixed with 80 mg of fibrinogen containing Factor XIII. A single intratumoral injection of the mixture was performed preoperatively under endoscopy in 20 patients with colorectal carcinoma. Postoperative histopathologic examinations revealed the formation of fibrin fibers at the site of injection and marked infiltration of inflammatory cells into the tumor stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…OK-432 is a non-specific immunopotentiator of bacterial origin that has been reported to induce cytotoxic CD4+ T cells in both mice and humans (Ozaki and Suginoshita, 1989;Ozaki et al, 1990;Nagaoka et al, 1992). In the present study, we generated cytotoxic CD4+ T lymphocytes from the TILs of thyroid cancer patients treated with our augmented immunisation protocol using OK-432/ fbg .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…OK-432 is a non-specific immunopotentiator of bacterial origin that has been reported to induce cytotoxic CD4+ T cells in both mice and humans (Ozaki and Suginoshita, 1989;Ozaki et al, 1990;Nagaoka et al, 1992). In the present study, we generated cytotoxic CD4+ T lymphocytes from the TILs of thyroid cancer patients treated with our augmented immunisation protocol using OK-432/ fbg .…”
Section: Resultsmentioning
confidence: 92%
“…This local immunotherapy effectively induces the marked infiltration of inflammatory cells into the tumour stroma on the day after injection and can contribute to tumour regression. We have also demonstrated that the regional lymph nodes of cancer patients receiving this local immunotherapy were a useful source of competent B lymphocytes for the establishment of human-human hybridomas (Baba et al, 1992;Yagyu et al, 1993), and we have established cytotoxic CD4+ T-cell clones from such lymph nodes (Nagaoka et al, 1992). In the present study, we generated cytotoxic CD4+ T cells from the tumour-infiltrating lymphocytes (TILs) of thyroid cancer patients who had received the intratumoral injection of OK-432 with fibrinogen.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The OK/IL-2AK cells produced T helper type-1 (Th1) cytokines TNF-a and IFN-g, and that Th2 cytokines, that is, IL-4 and IL-6, were not produced under these conditions. Monden et al (1992) demonstrated that the intratumoral injection of the mixture of OK-432 and fibrinogen enhanced the regression of colorectal cancer, in which a granulomatous hypersensitive response containing many giant cells was generated in the tumour stroma. That feature highly resembled the delayed-type hypersensitivity reaction, which is associated with Th1 responses.…”
Section: Discussionmentioning
confidence: 99%
“…OK-432 induced a markedly augmented antitumor effect on colorectal cancers when injected intratumorally together with fibrinogen [10]. This type of local immunotherapy is effective not only in inducing local tumor regression but also in activating various cell components of regional lymph nodes [11].…”
Section: Introductionmentioning
confidence: 97%